The Role of Literacy in Moderation of The Influence of Edecation Level, Economics Conditions, and Socio-Cultural Factors on Early Marriage in Malang Regency Community - Raden Ayu Ratihsari Maladewi; Inayati Dwiputri; Sugeng Hadi Utomo (International Journal of Management Research and Economics, 2026)
This study aims to analyze the influence of education level, economic conditions, and socio-cultural factors on early marriage, and to examine the role of literacy as a moderating variable in these relationships in Malang Regency. The research method uses a descriptive quantitative approach with survey techniques. The sample consisted of 287 respondents taken from the population of early marriage perpetrators in 2024. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results of the study indicate that: (1) Education level has a negative and significant effect on early marriage; (2) Economic conditions have a positive and significant effect on early marriage; (3) Socio-cultural factors have a positive and significant effect on early marriage; (4) Simultaneously, the three independent variables have a significant effect. Furthermore, the results of the moderation analysis revealed that literacy is proven to weaken the influence of economic conditions on early marriage. However, literacy actually strengthens the influence of socio-cultural factors on early marriage, and does not moderate the relationship between education and early marriage. The conclusion of this study confirms that early marriage is a multidimensional phenomenon. Preventive interventions must be holistic, not only through formal education and economic improvement, but also by developing critical literacy in society so that they can re-evaluate the cultural norms that encourage the practice of child marriage.